2021
DOI: 10.3390/ani11092689
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pets on Human Mental Health and Wellbeing during COVID-19 Lockdown in Malaysia

Abstract: The adverse impact of SARS-CoV-2 (COVID-19) on mental and physical health has been witnessed across the globe. Associated mental health and wellbeing issues include stress, social isolation, boredom, and anxiety. Research suggests human–animal interactions may improve the overall wellbeing of an individual. However, this has been less explored in Southeast Asian countries like Malaysia and the present study examined the effect of pets on the mental health and wellbeing of Malaysians during the lockdown, or mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 39 publications
4
57
0
Order By: Relevance
“…This third point of view is in line with other studies that indicate the usefulness of the pet in mitigating some psychological problems due to isolation during the pandemic, for example, with (I) the study by Gaifoner et al [38] indicating that pet owners reported significantly better coping self-efficacy, significantly more positive emotions, and better psychological wellbeing; (II) the study by Muller et al [42], highlighting that adolescents with pets reported spending more time with their pets during the pandemic, and frequently reported pet interactions as a strategy for coping with stress; (III) the study by Ratshen et al [48] highlighting that the human-animal bond is a construct that may be linked to mental health vulnerability in animal owners and showing that animal ownership seemed to mitigate some of the detrimental psychological effects of COVID-19 lockdown; (IV) the study by Bowen et al [46] showing that the quality of life of owners was strongly influenced by the lifestyle and emotional effects of the confinement and that pets provided them with substantial support to mitigate those effects.…”
Section: Discussionsupporting
confidence: 90%
“…This third point of view is in line with other studies that indicate the usefulness of the pet in mitigating some psychological problems due to isolation during the pandemic, for example, with (I) the study by Gaifoner et al [38] indicating that pet owners reported significantly better coping self-efficacy, significantly more positive emotions, and better psychological wellbeing; (II) the study by Muller et al [42], highlighting that adolescents with pets reported spending more time with their pets during the pandemic, and frequently reported pet interactions as a strategy for coping with stress; (III) the study by Ratshen et al [48] highlighting that the human-animal bond is a construct that may be linked to mental health vulnerability in animal owners and showing that animal ownership seemed to mitigate some of the detrimental psychological effects of COVID-19 lockdown; (IV) the study by Bowen et al [46] showing that the quality of life of owners was strongly influenced by the lifestyle and emotional effects of the confinement and that pets provided them with substantial support to mitigate those effects.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Mueller et al [ 50 ] confirmed that adolescents having pets reported spending more time with their pets during the pandemic, and frequently reported pet interactions as a strategy for coping with stress—they suggested that future research should explore the role of pets in coping with stress and social isolation during the pandemic. Grajfoner et al [ 51 ] also revealed the pets’ positive impact on human mental health and well-being; therefore, they propose the integration of pets in prevention, recovery, and intervention programs to promote mental health and well-being, especially during periods of prolonged social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous methods have been used in various study groups to mitigate COVID-19 related psychological and mental health issues. These methods include animal accompanied ( Grajfoner et al, 2021 ), spiritual and telehealth for palliative care ( Palmer et al, 2020 ), network building intervention ( Nooraie et al, 2021 ), Yoga ( Sahni et al, 2021 ) and others. However, a purposeful model for COVID-19 based on positive psychology core values has not been established.…”
Section: Introductionmentioning
confidence: 99%